Glycemic control of people with type 2 Diabetes mellitus in a Family Healthcare Unit in the interior of São Paulo (Research, Society and Development, 2021)
This study aimed to analyze the glycemic control of people with type 2 diabetes mellitus in a Family Healthcare Unit in the city of Araras, São Paulo. This is a descriptive cross-sectional study based on the collection of sociodemographic and clinical data from physical records. 102 participants were included, 66.6% were female and mean age was 61.4 years. It was shown that 57.8% had inadequate glycemic control with glycated hemoglobin equal to or greater than 7.0%. Inadequate glycemic control was associated with age group, polypharmacy and types of medication prescribed for the treatment of diabetes (p